Role Of Family For Children's Education During A Pandemic In Eastern Indonesia - et. al., Weldemina Yudit Tiwery , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The pandemic that occurred in Indonesia in general to the eastern part of Indonesia had devastated the children's future. Schools were closed; children will study from home with limited facilities. The availability of learning devices at home, including laptops, computers, cellphones, and internet quotas, are daily food for every student studying during the pandemic. Parents and families also experience pressure due to changes in children's learning patterns at home during the pandemic. Parents are required to assist when the child goes through the learning process at school until completing the teacher's assignments. As a result, the parents experience pressure due to the school's large number of tasks. The study aimed to determine parents' role in children's learning process at home during the pandemic period by taking samples from several regions in eastern Indonesia. The method used was a case study to reveal the situation of the object being analyzed. Subjects in the study were 75 parents who had elementary school-age children. 25 people were from North Maluku, 25 people were from Maluku and 25 people were from West Papua in February - April 2020 through telephone interview techniques and online questionnaire filling and analysis. The data used thematic data, analysis techniques that emphasize coding by referring to predetermined research questions. Secondary data get from documents, books, research results in the form of reports. Result of study show that implementation of education is the responsibility of parents. Family education is an option that students must undertake when a pandemic hits the country. Family education is an education in family life called the immediate environment or the first environment. Family is the first social group and plays a vital role in children's education. Family is the first and foremost place for children. Children spend more time with family than others. Parents and teachers' roles in the three provinces show that students' and teachers' teaching and learning processes during the pandemic period in Maluku were better than those taken from North Maluku and West Papua. This condition is affected by the ability to master information technology, the use of applications that make it more accessible and useful communication that can ensure optimal interaction between teachers, students, and parents because the process of interaction between parents and children is much more intense and open in Maluku by involving parents in school education during a pandemic.